Zig-zag-and-swirl : Alfred W. Lawson's quest for greatness - Henry, Lyell D., 1935- (University of Iowa Press, 1991)
Alfred W. Lawson (1869-1954) was a professional baseball player, inventor of the airliner, leader of a movement in the 1930's calling for the abolition of banks and interest, and founder of a utopian community, the so-called Des Moines University of Lawsonomy. This unusual institution, constantly embroiled in controversy in the 1940's and early 1950's, was dedicated not only to teaching Lawson's novel religious and scientific ideas but also to initiating a reform of human nature.